(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current practice of venipuncture procedures performed by laboratory technicians at the Department of Laboratory Medicine, District 1 Hospital, Ho Chi Minh City, in 2025. Methods: A descriptive cross-sectional quantitative study was conducted. A total of 384 venipuncture procedures performed by laboratory technicians at the Department of Laboratory Medicine were observed. A checklist was developed based on current regulatory documents and the venipuncture procedure of District 1 Hospital. Data were compiled and analyzed as percentages of correct, incorrect or incomplete implementation, and non-performance. Results: Core technical steps were performed at high rates, with most exceeding 95%. Specifically, tourniquet application, vein identification, and skin antisepsis at the puncture site were performed in 98% or more of observations; adequate antisepsis in terms of area and number of swabs reached 95,1%. Several shortcomings were identified, including hand hygiene before venipuncture, which was performed in only 47,1%, and the scoop technique for needle recapping, which was not performed in any observation (0/384). Regarding communication and patient instruction, explanation of the purpose of blood collection was provided in 50,5%, and post-procedure guidance in 58.6%, both markedly lower than technical performance indicators. No observed procedure fully complied with all required steps of the venipuncture process (0/384). Conclusion: Venipuncture procedures at District 1 Hospital were consistently performed with high adherence to core technical steps; however, improvements are needed in infection control practices and communication and patient education skills.